2010
DOI: 10.1108/13639511011066836
|View full text |Cite
|
Sign up to set email alerts
|

Officer's perception of organizational arrangements and preventive policing practice

Abstract: Purpose -The aim of the current study is three-fold: it aims to empirically investigates the relationship between officers' perceptions on organizational structure and preventive policing practices (PPP) in the South Korean context; it attempts to find what aspects of organizational characteristics will be influential in police officers' day-to-day activities;, utilizing structural equation modeling (SEM), it aims to identitify the complex networks of influences among various organizational aspects. Design/met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 30 publications
1
15
1
Order By: Relevance
“…However, demographic characteristics of the respondents closely reflected their actual distribution in the KNPA, as shown in Table I. The sample size of our study is quite large compared to previous studies conducted in Korea (Shim et al, 2015;Crow et al, 2012;Lee et al, 2010), which makes our data unique. Table I shows the demographic characteristics of respondents.…”
Section: Methodsmentioning
confidence: 77%
“…However, demographic characteristics of the respondents closely reflected their actual distribution in the KNPA, as shown in Table I. The sample size of our study is quite large compared to previous studies conducted in Korea (Shim et al, 2015;Crow et al, 2012;Lee et al, 2010), which makes our data unique. Table I shows the demographic characteristics of respondents.…”
Section: Methodsmentioning
confidence: 77%
“…All officers attending the class were asked to participate in the survey, and 60 officers out of 80 filled out the survey (response rate=75 percent). Since demographic characteristics of those two groups were similar (see Lee et al , 2010), two data sets were combined to increase sample size (total n =206).…”
Section: Methodsmentioning
confidence: 99%
“…COP has become a new paradigm of police organizations in the US; however, only 69 percent of large police agencies with COP policy (serving over 150,000 population) had clearly written COP policies or mission statements in 1999 (Hickman and Reaves, 2001). Recently, an empirical study found that explicit organizational philosophy significantly and positively influenced the practice of preventive policing among South Korean police officers through other organizational characteristics, such as reward system, flexibility, decentralization, and feedback mechanism (Lee et al , 2010). Thus, this study hypothesizes a positive relationship between officers' perception of explicit organizational philosophy and COP practice.…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations